Peran Coaching sebagai Moderator pada Hubungan antara Pelatihan dan Penugasan Hasil Pelatihan di Tempat Kerja - Endah Nuraini Hamdani (Journal of Management and Business Review, 2021)
Coaching is an employee development method that is widely used lately for various purposes, such as increasing competence at work, increasing the ability of students who are learning and increasing the effectiveness of training in companies. Not many studies have explored the role of coaching in the effectiveness of training, therefore this study aims to determine the effect of in-class training on the implementation of training results (project assignment) and to find out whether coaching acts as a moderator between in-class training by implementing the training results (Project Assignment). The main approach in this study using a quantitative approach, namely the data used in the form of numbers and analyzed quantitatively. The research data was taken from the results of the assessment of the MDP training. The amount of data obtained in this study was 131 participants. The analysis used for data processing is Moderate Regression Analysis (MRA). The results of the analysis using MRA show that coaching acts as a moderator Quasi variabel, meaning that coaching together with In Class Training results in an increase in the ability to do a better project assignment (PA). The ability to do project assignments includes the ability to make PA reports and make presentations